Employee equity incentive, executive psychological capital, and enterprise innovation - Yu, Liping; Hu, Jiabin (Frontiers in Psychology, 2023)
The input and deployment of human resources, such as senior executives and the core employees involved in different innovation processes, is key to developing enterprise innovation activities. Under the same framework, it is crucial to explore how employee equity incentive and senior executives' psychological capital affect enterprise innovation. This paper’s research sample comprises listed companies that implemented equity incentives in the A-share market from 2010 to 2021, examining the relationship between executive psychological capital, and enterprise innovation. This study found that:(1)Employee equity incentive and executives’ psychological capital can significantly improve the quality of innovation output while promoting enterprises to increase the quantity of innovation outputs; (2)Executive psychological capital contributes to the intermediary effect between employee equity incentive and enterprise innovation;(3)R&D investment has a positive moderating effect on employee equity incentive, senior executives' psychological capital and enterprise innovation; (4)The innovation incentive effect brought by the implementation of stock options by enterprises is more significant, which also makes the psychological capital of executives maintain a positive role in enterprise innovation;(5)In addition, the positive effects of employee equity incentive and executive psychological capital on enterprise innovation are affected by different property rights. The positive effects of employee equity incentive and executive psychological capital on enterprise innovation in state-owned enterprises are not high.